Analisis Pengaruh Hambatan Samping Terhadap Kinerja Ruas Jalan Perkotaan (Studi Kasus : Simpang SKA Sampai Simpang Tuanku Tambusai – Sudirman, Pekanbaru) - Nduru, Rikson; Alwinda, Yosi; Sebayang, Mardani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Tuanku Tambusai street is a road with many road side activities such as pedestrians, public transport stops and other vehicles as well as vehicles going in and out of land side roads. Those activities that have an impact on traffic flow problems such as congestion, therefore an analysis is needed due to the influence of side barriers on road performance. This research was conducted on the road section of the SKA intersection to Tuanku Tambusai street – Sudirman with two directions and four road segments. All data taken in the field are primary data such as road geometrycal conditions, vehicle flow volume, side barriers, travel speed. While secondary data are population and research location maps. Based on the results of the analysis and discussion, the most influential side barriers to the performance of road sections are the side barriers of vehicles entering and exiting with a contribution of 53 - 91%. The influence is carried out by the diversion of the side barriers of the vehicle exit/entry, it is found that there is an increase in the capacity of the east road with range of 206 - 362 pcu/hour daily and the west road with range of 33 - 231 pcu/hour daily, a decrease in the degree of saturation to the east road with range of 0.35 - 0.073 and the west road with ranged of 0.006 - 0.063, an increase in vehicle travel speed of the east road with ranged of 3 - 4 km/hour and the west road with ranged of 0.5 - 6 km/hour, and an increase in Level Of Service to A level has characteristics of free flow, low volume, high speed. Keywords: Side Barriers, Road Performance, Level Of Service